2021
DOI: 10.1093/molbev/msab306
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolutionary Signals IdentifyBurkholderia pseudomalleiSurvival Strategies in a Hostile Environment

Abstract: The soil bacterium Burkholderia pseudomallei is the causative agent of melioidosis and a significant cause of human morbidity and mortality in many tropical and subtropical countries. The species notoriously survives harsh environmental conditions but the genetic architecture for these adaptations remains unclear. Here we employed a powerful combination of genome-wide epistasis and co-selection studies (2,011 genomes), condition-wide transcriptome analyses (82 diverse conditions), and a gene knockout assay to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…In a prospective study of community-acquired sepsis from Ubon Ratchathani, the three commonest bacterial pathogens recovered from blood cultures were Escherichia coli, B. pseudomallei and Staphylococcus aureus , respectively, with a substantially higher mortality in the patients with melioidosis [36]. Studies of B. pseudomallei using genomics, transcriptomics and gene knockout assays have provided important novel insights into the evolution and survival of B. pseudomallei in harsh environments, supporting the hypothesis that nutrient-limited conditions have been the common selection pressure acting on this species [37 ▪ ].…”
Section: Epidemiologymentioning
confidence: 80%
“…In a prospective study of community-acquired sepsis from Ubon Ratchathani, the three commonest bacterial pathogens recovered from blood cultures were Escherichia coli, B. pseudomallei and Staphylococcus aureus , respectively, with a substantially higher mortality in the patients with melioidosis [36]. Studies of B. pseudomallei using genomics, transcriptomics and gene knockout assays have provided important novel insights into the evolution and survival of B. pseudomallei in harsh environments, supporting the hypothesis that nutrient-limited conditions have been the common selection pressure acting on this species [37 ▪ ].…”
Section: Epidemiologymentioning
confidence: 80%
“…Findings of higher numbers of B. pseudomallei in deeper soil horizons below 30 cm (Manivanh et al, 2017) strengthen the hypothesis that low nutrient levels correlate with the abundance of B. pseudomallei. Recently, Chewapreecha et al (2022) suggested genetic adaptation of B. pseudomallei to nutrient depletion during evolution based on their extensive genomic and transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of travel history for the two Texas cases and phylogeographic analysis of the infecting strains strongly suggest these two infections were independently acquired from the local environment in Texas. Detecting B. pseudomallei in the environment has been historically challenging due to the incomplete understanding of its optimal habitat (e.g., soil composition, moisture content, presence of competing bacteria [29][30][31]). However, our findings are consistent with the idea that B. pseudomallei is quite rare in the environment in this region of Texas.…”
Section: Discussionmentioning
confidence: 99%